Oblique in Translation of Literary Texts - Haitham Mehdi Maatoq ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The current study investigates the textual competence in One Hundred Years of Solitude as translated into Arabic. For Al-Emara, the translator’s task is to consider the procedures of textual competence in order to achieve translation competence. One Hundred Years of Solitude (chapter 3) has been selected as a recognized sample. Two translators (Mahmud Maseud & Salih Ealamni) have been chosen for this plan. The comparison is made between the translations based on Al-Emara’s approach. Out of the present study, it is noted that Ealmani’s translation is more competence than Maseud’s. In other words, the former conveys the textual competence of the original in his translation. Still, it is concluded that every translator must be authoritarian in his commitment to the original text .This could be accomplished by applying Al-Emara’s textual competence. Note: MLA citation is used for this research (the update version does not include a year inside the thesis). Also, According to MLA style, data that are taken from social networks do not need citation because they are viewed as common knowledge.